2014
DOI: 10.1186/1556-276x-9-684
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing oral bioavailability of quercetin using novel soluplus polymeric micelles

Abstract: To improve its poor aqueous solubility and stability, the potential chemotherapeutic drug quercetin was encapsulated in soluplus polymeric micelles by a modified film dispersion method. With the encapsulation efficiency over 90%, the quercetin-loaded polymeric micelles (Qu-PMs) with drug loading of 6.7% had a narrow size distribution around mean size of 79.00 ± 2.24 nm, suggesting the complete dispersibility of quercetin in water. X-ray diffraction (XRD) patterns illustrated that quercetin was in amorphous or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
72
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(90 citation statements)
references
References 40 publications
11
72
0
Order By: Relevance
“…9,10) The copolymer exhibits an amphipathic property attributed to its hydrophilic and hydrophobic residues, which could contribute to the formation of micelles in water. Unlike conventional polymers such as polyvinylpyrrolidone and hydroxypropyl methylcellulose, Soluplus ® is bifunctional and can act as both a polymeric carrier of solid dispersions and as a solubilizer through the formation of micelles in water, [11][12][13] which could be useful for the production of highly water-soluble formulations. Furthermore, the polymer has an inherent binding site that allows hydrogen bonding and/or van der Waal's interactions with drug molecules, which can lead to the stabilization of the drug molecule in the matrix.…”
mentioning
confidence: 99%
“…9,10) The copolymer exhibits an amphipathic property attributed to its hydrophilic and hydrophobic residues, which could contribute to the formation of micelles in water. Unlike conventional polymers such as polyvinylpyrrolidone and hydroxypropyl methylcellulose, Soluplus ® is bifunctional and can act as both a polymeric carrier of solid dispersions and as a solubilizer through the formation of micelles in water, [11][12][13] which could be useful for the production of highly water-soluble formulations. Furthermore, the polymer has an inherent binding site that allows hydrogen bonding and/or van der Waal's interactions with drug molecules, which can lead to the stabilization of the drug molecule in the matrix.…”
mentioning
confidence: 99%
“…Second, because of the viscosity properties of Sco-Ms, the Sco-Ms could adhere to the intestines and increase the contact area and contact time between the drug and GI tract, which contributed to the enhanced absorption of scopoletin. Third, studies have reported that nanoparticles with sizes approximately at or below 100 nm show optimum cellular and nuclear uptake in smooth muscle and epithelial cells [20,32] . In addition, another previous study indicated that phase II metabolism might be one of the reasons for the poor bioavailability of scopoletin [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Three groups of rats were orally administered with scopoletin suspension, Sco-PM or Sco-Ms at an equivalent dose of 100 mg/kg scopoletin. The blood samples (approximately 0.3 mL) were collected via the orbital venous plexus at predetermined time intervals (2,5,10,15,20,30,45,60,90, and 120 min). All blood samples were immediately centrifuged at 3000×g for 5 min, and then the plasma supernatant was collected.…”
Section: Pharmacokinetic and Biodistribution Studymentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Micelles formulated with soluplus have a low critical micelle concentration value (about 10 -8 M) and small in size (~65 nm). 7 In the molecular structure, soluplus has a hydrophilic polyethylene glycol backbone and several hydrophobic vinylcaprolactam/vinyl acetate side chains. Its hydrophobic carbonyl group can form hydrogen bonds with the hydroxyl groups of drug molecules, thus increasing the drug loading (DL) capacity and the stability of the micelles.…”
Section: Introductionmentioning
confidence: 99%